Weight management recommendations for youth with Down syndrome: Expert recommendations - Ptomey, Lauren T.; Oreskovic, Nicolas M.; Hendrix, James A.; Nichols, Dominica; Agiovlasitis, Stamatis (Frontiers in Pediatrics, 2023)
Youth with Down syndrome (DS) have a higher prevalence of overweight and obesity compared to the general youth population. Due to physiological and cognitive differences observed in youth with DS, weight management recommendations developed for the general population, may not be suitable for youth with DS. However, there are no recent recommendations for weight management in youth with DS. A workgroup of clinicians and researchers with extensive experience working with youth with DS came together to give medical providers and families guidance for weight management in youth with DS. Recommendations were developed by the workgroup via a methodical, deliberative process. After the initial development of the recommendations, they were shared with an expert review panel and caregivers who rated the strength of the recommendation and strength of the evidence. The workgroup moved forward the recommendations which the review panels rated as strong. Eight recommendations were developed which focused on screening for overweight and obesity, screening for health conditions that may impact dietary intake and physical activity, screening for feeding difficulties, setting appropriate recommendations for dietary intake and physical activity, and well as prevention and treatment of overweight and obesity using evidence-based strategies. These recommendations can be implemented by clinicians working with youth with Down syndrome as well as the family, school, and other relevant entities.